Sliding Mode Control of the Battery Bank for the Fuel Cell-based Distributed Generation System - Junsheng Jiao (Institute of Advanced Engineering and Science, 2013)
The dynamic models for the fuel cell power and the configuration of the fuel cell distributed generation system are shown in this paper. Due to nonlinear characteristics of fuel cell model, the output voltage of fuel cell varies greatly when the load changes. A novel interface is designed to provide a constant output voltage for charging of the battery bank of the fuel cell distributed generation. The thesis presents a sliding mode control design of PEMFC distributed generation system. A cascaded control structure is chosen for ease of control realization and to exploit the motion separation property of power converters. The simulation results confirm the output current and voltage of the PEM fuel cell array converge rapidly to their reference values. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3594